(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2026)
Researchers in the field of medicinal chemistry have focused their efforts on developing safer and less toxic pharmaceutical compounds for treating type 2 diabetes, compounds that can be used long-term without causing serious side effects. This study focused on the synthesis of two new imidazole derivatives using an alkaline medium and DMSO as a solvent. Good yields were obtained, and the chemical structure of the synthesized compounds was confirmed using infrared (IR) spectroscopy and proton-carbon nuclear magnetic resonance spectroscopy (1H NMR and 13C NMR). The results showed complete agreement with the theoretically predicted structures. In addition, two theoretical studies were conducted on the synthesized compounds, including density functional theory (DFT) calculations and molecular docking studies of the SIRT1 and GSK3β proteins. The results of these studies were then correlated with the analysis of the theoretical data. The results showed that compound 3β was the most effective of the synthesized compounds.